Transcriptome Analysis Revealed a Cold Stress-Responsive Transcription Factor, PaDREB1A, in Plumbago auriculata That Can Confer Cold Tolerance in Transgenic Arabidopsis thaliana - Li, Wenji; Gao, Suping; Lei, Ting; Jiang, Liqiong; Duan, Yifan; Zhao, Zian; Li, Jiani; Shi, Lisha; Yang, Lijuan (Frontiers in Plant Science, 2022)
The tropical plant Plumbago auriculata can tolerate subzero temperatures without induction of apoptosis after cold acclimation in autumn, making it more cold tolerant than conventional tropical plants. In this study, we found that low temperatures significantly affected the photosynthetic system of P. auriculata. Using transcriptome sequencing, PaDREB1A was identified as a key transcription factor involved in the response to cold stress in P. auriculata. This transcription factor may be regulated by upstream JA signaling and regulates downstream ERD4 and ERD7 expression to resist cold stress. Overexpression of PaDREB1A significantly enhanced freezing resistance, protected the photosynthetic system, and enhanced the ROS scavenging mechanism under cold stress in Arabidopsis thaliana. Additionally, PaDREB1A significantly enhanced the expression of CORs and CAT1 in A. thaliana, which further activated the downstream pathway to enhance plant cold tolerance. This study explored the possible different regulatory modes of CBFs in tropical plants and can serve as an important reference for the introduction of tropical plants to low-temperature regions.